2015
DOI: 10.1111/ijcp.12624
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide time trends and risk factors for in-hospital falls-related major injuries

Abstract: In-hospital falls-related major injuries increased significantly during the study period. Elderly with dementia, osteoporosis, stroke, depression, chronic obstructive pulmonary disease and Parkinson disease were associated with increased OR for in-hospital fall-related major injuries. Increased focus on patients with these comorbidities is warranted to decrease the increasing incidence in in-hospital major injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Additional hospital stay costs are estimated to range between £3332 and £27 468 per fall, depending on the injury 12. This is consistent with international studies which report rates of major inhospital fall injuries have increased over the last decade in Denmark13 and that rates of injurious falls remain unchanged in the USA 14. In Australia, an inhospital fall is associated with an increase in hospital stay of 8 days, and $A6669 additional hospital costs 15…”
Section: Introductionsupporting
confidence: 76%
“…Additional hospital stay costs are estimated to range between £3332 and £27 468 per fall, depending on the injury 12. This is consistent with international studies which report rates of major inhospital fall injuries have increased over the last decade in Denmark13 and that rates of injurious falls remain unchanged in the USA 14. In Australia, an inhospital fall is associated with an increase in hospital stay of 8 days, and $A6669 additional hospital costs 15…”
Section: Introductionsupporting
confidence: 76%
“…Poor mobility, leads to unsteady gait and falls [7,54,55]. Falls are a major cause of morbidity in the elderly and even if they survive, fractures can lead to high medical costs from hospitalization [3]. The risk of fall related injuries increases with age [5,56].…”
Section: Discussionmentioning
confidence: 99%
“…One in every three adults ages 65 and older falls each year [2]. In 2010, 2.4 million non-fatal fall injuries in older adults were treated in emergency rooms and over 22,000 older adults died from unintentional fall injuries [3]. The length of hospital stay is about twice that of a younger person after a fall [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fall‐related injuries and the associated need for interventions and treatment may further prolong hospital length of stay and increase healthcare costs (Morello et al., ; Titler et al., ). In a large Danish study of patients aged ≥65 years that sustained an in‐hospital fall, spanning over a decade, 17% incurred a major injury that required surgery or intensive observations (Jørgensen et al., ), and a 10‐year Australian cohort study reported an 18% incidence of fractures following an in‐hospital fall (Brand & Sundararajan, ).…”
Section: Introductionmentioning
confidence: 99%